An ectomesenchymal chondromyxoid tumour on the lateral border of the tongue. Issue 10 (October 2020) - Sakurai, K.; Nakamori, K.; Yamazaki, M.; Tanuma, J.-I.
Abstract: Ectomesenchymal chondromyxoid tumour (ECT) is an extremely rare intraoral mesenchymal tumour. Most of these tumours have been identified on the anterior aspect of the dorsal surface of the tongue. ECT is difficult to diagnose because of its rarity. We report a case of ECT arising on the lateral border of the tongue in a 67-year-old woman. The tumour, measuring 20 × 10 mm in size, was surgically removed. Histopathologically, the tumour was composed of small polygonal cells arranged in sheets, with a myxoid or hyalinized stroma. The tumour boundary was clear; however, the tumour showed a multinodular structure expanding along the tongue surface without obvious capsule. Careful examination revealed the tumour nodule to be spreading in a skip lesion-like fashion away from the main part of the tumour in the striated muscle layer. Although there was no evidence of recurrence at 18 months after the surgery, our observations suggest that surgery for ECT resection with a safety margin is more appropriate than enucleation.